Aplikasi Berbagai Bahan Asal Hormon Alami terhadap Penyetekan Kenanga - Nurul Istiqomah; Noraida Hayati; Fenny Erawati (Rawa Sains: Jurnal Sains STIPER Amuntai, 2012)
Cananga flowers can be taken cananga oil and ornamental flowers. Cananga can be reproduced generatively. Vegetative propagation is still difficult, both with cuttings, grafts, grafting and tissue culture. Plant propagation by cuttings, a problem that is often faced is the difficulty of cuttings in forming roots, to overcome this problem can be used to grow stimulants that can stimulate rooting cuttings. Hormones are growth stimulants which naturally occur in plants both in leaves and fruit, one of which is in coconuts. The purpose of this study was (i) to determine the effect of various natural hormone ingredients on the growth of cananga cuttings, and (ii) to obtain the best natural hormone ingredients that influence the growth of cananga cuttings. This research was carried out on STIPER Amuntai land and greenhouses from July to August 2012. This experiment used a single randomized block design (RBD), grouping based on plant sires. The factors studied were various natural hormone ingredients (H), consisting of 4 levels, namely: h1 = old coconut water, h2 = young coconut water, h3 = red onion and h4 = cow urine. Each treatment consisted of 4 treatments and 6 groups, so that there were 24 experimental units. The experimental results show that the application of various natural hormones is not able to increase the growth of cananga cuttings. The best natural hormones are not obtained even though by observation of natural hormones that are able to maintain vigority cuttings better is young coconut water (h2).